Letters to Florence O'Donoghue from various individuals (F - G) in response to the publication of his serial on Liam Lynch, and queries and newspaper advertisements seeking information on Liam Lynch, - O'Donoghue, Florence, 1895-1967 (1953)
Correspondents are Seamus Finn, D. Finucane, Gerald Fitzgerald, Peadar Glynn and James Griffin.